Samtliga bokrecensioner - * * * (Lychnos, 2012)
Ahlberger, Christer, Henric Bagerius, Carl Holmberg, Ulrika Lagerlöf Nilsson, Pia Lundqvist, Tomas Nilsson & Brita Planck (red.): Historier. Arton- och nittonhundratalens skönlitteratur som historisk källa (Simon Larsson)